Upaya Meningkatkan Hasil Belajar PKN Siswa Kelas XI BKP1 dengan Menggunakan Model Pembelajaran Kooperatif Tipe Jigsaw di SMK Negeri 2 Karang Baru - Irwani (Tematik: Jurnal Penelitian Pendidikan Dasar, 2022)
This Classroom Action Research (CAR) was carried out considering the importance of efforts to improve the quality of learning outcomes through various ways or optimal learning strategies, where the teacher plays a very important role in preparing students to take part in learning. The Problem Based Learning model was chosen to improve the ability to solve the problem of the Dynamics of Implementation of Pancasila Democracy in Civics Subjects in class XI BKP1 of SMK Negeri 2 Karang Baru, Even Semester of TP. 2021/2022. This is deemed very necessary because interest and motivation and student learning outcomes in the class are still low. The subjects of this study amounted to 30 people. The research data was obtained by using a performance test in the form of student observation sheets. From student learning outcomes, data obtained in the first cycle of students' courage in asking questions and expressing opinions increased from 70.33% to 85.55%, an increase of 15.22%